A Polyoxovanadate as an Advanced Electrode Material for Supercapacitors. Issue 10 (9th May 2014) - Chen , Han‐Yi; Wee , Grace; Al‐Oweini, Rami; Friedl , Jochen; Tan, Kim Soon; Wang, Yuxi; Wong , Chui Ling; Kortz, Ulrich; Stimming, Ulrich; Srinivasan, Madhavi
Abstract Polyoxovanadate Na6V10O28 is investigated for the first time as electrode material for supercapacitors (SCs). The electrochemical properties of Na6V10O28 electrodes are studied in Li+‐containing organic electrolyte (1 M LiClO4 in propylene carbonate) by galvanostatic charge/discharge and cyclic voltammetry in a three‐electrode configuration. Na6V10O28 electrodes exhibit high specific capacitances of up to 354 F g−1. An asymmetric SC with activated carbon as positive electrode and Na6V10O28 as negative electrode is fabricated and exhibits a high energy density of 73 Wh kg−1 with a power density of 312 W kg−1, which successfully demonstrates that Na6V10O28 is a promising electrode material for high‐energy SC applications.